Komunikasi Pemasaran Terpadu Pariwisata Berbasis Kearifan Lokal Di Kota Bogor - Ratih Siti Aminah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
The growing of tourism in Bogor is very competitive. The Companies have to produce the interest products for consumers and should communicate effectively with the stakeholders. Therefore a company should be able to develop appropriate marketing strategies to cope with increasingly fierce competition. The concept is to apply the importance of a company in integrating various communication channels to closely integrate multiple channels of communication to deliver a message by clear, consistent, and exciting about the organization and its brand. Kujang Pajajaran Gallery Bogor is one of the tourism place that implements the concept of integrated marketing communications in attracting tourists to visit.This research is a qualitative descriptive study using in-depth interviews, observation, documentation, and literature. The material processing techniques using an interactive model that was introduced by Miles and Huberman which includes three The material components namely reduction, presentation, drawing conclusions and verification.The results showed that Kujang Padjajaran Gallery Bogor utilizationed three elemen of integrated marketing communication such as marketing interactive, personal selling and selling promotion.